A Singular Opportunity: Setting Standards for Victim Assistance under the Treaty on the Prohibition of Nuclear Weapons. Issue 1 (18th February 2021) - Docherty, Bonnie
Abstract: With the Treaty on the Prohibition of Nuclear Weapons (TPNW) having entered into force on 22 January 2021, the time has come for states parties to start operationalizing its obligations. The TPNW not only bans nuclear weapons but also includes provisions designed to reduce the 'unacceptable suffering' caused by past use and testing. These positive obligations require states parties to assist victims, remediate the contaminated environment, and provide international cooperation and assistance to support those efforts. To inform the work of the TPNW's First Meeting of States Parties, which will start the implementation process, this commentary proposes strong standards for assisting victims in a nuclear weapons context. The standards draw on the TPNW's language, humanitarian disarmament's victim assistance norms, and principles for assisting victims of toxic remnants of war. This commentary addresses the types of harm, types of assistance, framework of shared responsibility, implementation measures, and guiding principles that constitute an effective and feasible assistance program for nuclear weapon victims. Collectively the proposed standards aim to advance the humanitarian purpose of the TPNW. Abstract : The Treaty on the Prohibition of Nuclear Weapons not only bans nuclear weapons but also includes provisions designed to reduce the 'unacceptable suffering' caused by past use and testing.